(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This paper analyses the most significant issues that the Court of Cassation has tackled in its Order n. 27325/2021, which deals with the protection of participants’ data in the framework of scientific research and the complex dimension of biobanks and the related genetic databases. Special emphasis is put on informed consent and informational self-determination, in the context of bankruptcy and the purchase of the biobank by a new data controller. Subsequently, some considerations are expressed about the impact of the hypothetical application of the GDPR to the case and, finally, some solutions to tackle the current challenges are suggested.